VD_FINDINFO Décision / 2011 / 774 vom 21. Dezember 2011 - VD Tribunal cantonal (2011)
DÉCISION SUR FRAIS, DÉPENS, LOI FÉDÉRALE SUR L'ASSURANCE-ACCIDENTS | 61 let. a LPGA, 61 let. g LPGA, 52 LPA-VD, 55 al. 1 LPA-VD, 94 al. 1 let. c LPA-VD